2023
DOI: 10.2186/jpr.jpr_d_21_00333
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives of residual ridge resorption: Pathological activation of oral barrier osteoclasts

Abstract: Tooth extraction is a last resort treatment for resolving pathological complications of dentition induced by infection and injury. Although the extraction wound generally heals uneventfully, resulting in the formation of an edentulous residual ridge, some patients experience long-term and severe residual ridge reduction. The objective of this review was to provide a contemporary understanding of the molecular and cellular mechanisms that may potentially cause edentulous jawbone resorption. Study selection: Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…In a mouse model, physiological mechanical damage from mastication induced IL-6 production from gingiva, thereby resulting in accumulation of gingiva-resident T helper 17 (Th17) cells at the oral mucosal barrier [42]. The cyclic pressure-induced secretion of cytokines from hGFs observed in this study could thus be partly explained as an intrinsic mechanism in the gingiva to condition local osteoimmunity [43]. It will be of interest and important to analyze the effects of cyclic pressure-induced hGF factors, including anti-inflammatory cytokines, on osteoclasts together with osteoblasts and other immune cells, such as Th17 cells.…”
Section: Discussionmentioning
confidence: 62%
“…In a mouse model, physiological mechanical damage from mastication induced IL-6 production from gingiva, thereby resulting in accumulation of gingiva-resident T helper 17 (Th17) cells at the oral mucosal barrier [42]. The cyclic pressure-induced secretion of cytokines from hGFs observed in this study could thus be partly explained as an intrinsic mechanism in the gingiva to condition local osteoimmunity [43]. It will be of interest and important to analyze the effects of cyclic pressure-induced hGF factors, including anti-inflammatory cytokines, on osteoclasts together with osteoblasts and other immune cells, such as Th17 cells.…”
Section: Discussionmentioning
confidence: 62%
“…It has been well established that tooth extraction induces not only bone regeneration and remodeling by osteoclasts in the bony socket but also a unique set of osteoclasts on the surface of alveolar bone ( Kondo et al, 2022 ). Histologically, osteoclasts are distinct as multinuclear large cells adhered to the bone lacunae.…”
Section: Resultsmentioning
confidence: 99%
“…N-BP adsorbed on bone mineral stays relatively firmly until bone resorption by osteoclasts, and active bone resorption may release N-BP from bone surface to the local environment. Tooth extraction induces not only bone remodeling in the bony socket but also unusual osteoclastogenesis on the external surface of alveolar bone ( Kondo et al, 2022 ). The present study demonstrated the oral barrier inflammation of ZOL-pretreated mice, which was densely localized adjacent to the alveolar bone surface ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts that interface the oral barrier tissues remain active in the alveolar crest during wound healing in the tooth extraction socket, 38 , 39 and various cytokines and chemokines are involved in the immune response after tooth extraction. 40 Therefore, chemokine expressions in the healing gingival tissue at the crest of the alveolar ridge should be investigated.…”
Section: Discussionmentioning
confidence: 99%